Unprecedented Hole Concentration of NiSe2 Electrodes Leading to Hole Degeneration of Entire WSe2 Channels - Bae, Ji Kwon; Ghods, Soheil; Cho, Hyeon Ho; Jang, Hochan; Kim, Seung Il; Lee, Jae Hyun; Yu, Hak Ki (Nano Letters, 2024)
Semimetal electrodes for 2D semiconductors have been extensively studied; however, research on p-type semimetals has been limited due to the scarcity of materials that satisfy both high work functions and low resistances. In response, we investigated the behavior of NiSe2 as an electrode. Utilizing a novel co-evaporation method that suppresses oxidation and contamination, we synthesized NiSe2 demonstrating a high work function of 5.53 eV, a low resistance of 5.81 × 10-5 Ω cm, and a record hole concentration exceeding 1023 cm-3. We confirmed that when WSe2 comes into contact with NiSe2, the Fermi level of WSe2 falls below the work function of NiSe2, leading to complete hole degeneration of the channel. This unusual Fermi level alignment correlates with the high hole concentration in NiSe2 and the maximum energy level of its hole pockets. Our research provides new insights into how an electrode’s hole concentration affects channel behavior.
Keywords: Co-evaporation method; Energy; High work function; Low resistance; P-type; P-type device; P-type electrode; Synthesised; WSe2 FET; hole concentration; NiSe2; p-type device; p-type electrode; semimetal; WSe2 FET